Critical Region Identification of Cable-Stayed Bridges Based on Eigensensitivity - Jiajing Li; Meng Meng; Qiaoyun Wu (Buildings)
Conducting health monitoring on entire large-scale structures is challenging. Compared to non-critical regions, local damage in critical regions significantly impacts the overall structural performance, with even minor damage posing a threat to structural safety. Therefore, identifying the critical regions of a structure is essential to enable prioritized and focused monitoring, evaluation, and management. This paper proposes a method for identifying critical regions in cable-stayed bridges based on dynamic eigensensitivity analysis. The method integrates the sensitivity of multi-order eigenvalues and eigenvectors with respect to elemental stiffness parameters, designating regions with high sensitivity values as critical. The results demonstrate that the midspan region of the main girder, the longest stay cable, and the junctions between the upper, middle, and lower bridge towers and the foundation are identified as critical regions in a cable-stayed bridge. These findings are consistent with established engineering experience. The proposed critical region identification method holds significant potential for improving the efficiency of health monitoring and assessment, as well as optimizing the allocation of manpower and material resources.